2008
DOI: 10.1177/0145482x0810200407
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Perspectives of Teachers and Parents on the Literacy Media Selections for Independent Study of Students who are Visually Impaired

Abstract: This study explored the choices of literacy media for independent study of students with visual impairments. The predictors that were taken into account were teachers' use of technology, experience in teaching, and mastery of braille and the knowledge of braille of students, parents, and close friends.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 16 publications
1
8
0
1
Order By: Relevance
“…Some Canadian government programs that provide adaptive computer technologies to students with visual impairments for off-campus use offer only one type of technology-text-to-speech screen readers, for example. As Argyropoulos, Sideridis, and Katsoulis (2008) noted, there has been little research on the extent to which postsecondary students with visual impairments use one type of adaptive computer technology or several. Therefore, we examined the adaptive computer technologies used by students who indicated that they were blind and those who indicated that they had low vision.…”
mentioning
confidence: 99%
“…Some Canadian government programs that provide adaptive computer technologies to students with visual impairments for off-campus use offer only one type of technology-text-to-speech screen readers, for example. As Argyropoulos, Sideridis, and Katsoulis (2008) noted, there has been little research on the extent to which postsecondary students with visual impairments use one type of adaptive computer technology or several. Therefore, we examined the adaptive computer technologies used by students who indicated that they were blind and those who indicated that they had low vision.…”
mentioning
confidence: 99%
“…It is argued that the lack of teachers’ training in AT constitutes one of the main reasons why it is being underutilized from both students with VI and their teachers. Despite the fact that teachers recognize the significance of using AT, most of them believe they have inadequate skills to integrate AT into their teaching (Abner & Lahm, 2002; Argyropoulos et al, 2008; Kapperman, Sticken, & Heinze, 2002; Tsiakali & Argyropoulos, 2015; Zhou et al, 2011). According to the United Nations Educational, Scientific and Cultural Organization (UNESCO; 2009), people with visual disabilities are having serious problems while using AT because of the lack of basic Information and Communication Technology (ICT) skills, lack of training, and lack of training materials.…”
Section: Discussionmentioning
confidence: 99%
“…The authors developed a descriptive survey with items and questions from instruments that have been used by other researchers (Argyropoulos et al, 2008; Erin et al, 2006; Lusk & Corn, 2006). The questionnaire consisted of two main parts: demographic characteristics (first part) and choices of literacy mediums for study (second part).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advances in new technologies are gradually being implemented, like in the study of Argyropoulos, Sideridis, and Katsoulis (2008). A notable example is the multimedia format 'Daisy' (Ribere and Moese 2008), which integrates text, sound, images and video in a synchronised sequence.…”
Section: Teaching Pictorial Work To Students With Visual Disabilitiementioning
confidence: 99%